Islam in China - Frankel, James D. (London)
ix, 193 sayfa
Keywords: “In China there are up to 25 million Muslims living in the country, representing over 1200 years of Chinese-Islamic relations. However, little is known about the historical and contemporary geopolitical relations between China and the Muslim world, or the situation for the diverse groups of Muslims living in China today. In this book, James Frankel studies the rich and dynamic history of Muslims in China from the Tang dynasty (618-907) to the present day. He shows that Muslims in China remain an internally diverse population separated geographically, ethnically, linguistically, economically, educationally, and along sectarian and kinship lines. But despite having its own local flavours and accents, Islam in China is recognisable as the same religious tradition practiced by approximately 1.8 billion Muslims worldwide and Muslims in China are inextricably part of society, living alongside other minorities and amongst the great Han Chinese majority. Tracing 1200 years of history, this book shows that Muslim communities in China have undergone tremendous change, touched by the forces of Chinese history, the development of Islamic traditions outside China, and geopolitics. In highlighting the paradoxical situation in which Chinese Muslims have found themselves - living as both insiders and outsiders to Chinese society and state - the book examines why after so many centuries of habitation and naturalisation, Muslims in China are still stigmatized by their perceived alien origins. The book follows the 'yin and yang' of compatibility and difference and the connections and ruptures between two great civilisations“ --